TI_GERICHTE 52.2005.271 vom 5. September 2005 , Obbligo di rimboscare l'area boschiva - irricevibilità del ricorso - TI Tribunale d'appello (2005)
Obbligo di rimboscare l'area boschiva - irricevibilità del ricorso